A Unified Knowledge-Based Content Management Framework towards Value-Added Application and Service Development and Business Marketing for Museums: The Case Study of the National Museum of Natural Science in Taiwan. (March 2014) - Hsu, Tien-Yu; Yeh, Jen-Yuan
Abstract : The practices of knowledge management ( KM ) are complicated and usually difficult of accomplishment. In most situations, KM is introduced on a departmental or even individual level, leading to the Content Silo Trap where content, applications, and services are created in isolation. To address the issue, this paper proposes, for museums, a Unified Knowledge-based Content Management Framework, which consists of the Unified Process of Knowledge Content Development, the Multi-layered Reusable Knowledge Content Structures, and the Unified Knowledge-based Content Management System. The first declares tasks for the museum staff to perform while building and utilizing knowledge. The second abstracts content in consistent structures for reuse. The last comprises subsystems serving functionalities for knowledge-based content management. The proposed framework has been successfully introduced in the National Museum of Natural Science to manage tasks and operations on a daily basis. In addition, a platform based on the framework is implemented to support knowledge-based content management, value-added application and service development, and business marketing. The overall practical experience is a valuable reference for museums, the academia, and the industry.